Dialog Kebudayaan Menuju Ko-Eksistensi Damai Antarperadaban - Budiono Kusumohamidjojo (STF Driyarkara - Diskursus, 2011)
Abstract: Culture is the totality of the human expression towards realization of itself individually and collectively and has always been a platform for humans to achieve life ideals. As culture cannot escape its temporal and spatial circumstances there exists the plurality of cultures and the ensuing relativity of values. These dynamics have led humankind to become entrapped in Huntington’s “conflict of civilizations” i.e. a conflict of values. The world of the early 21st century is dominated by “Western civilization,” the “Sinic civilization” and increasingly by “Islamic civilization.” Although language and technology have brought humans closer to each other, language and technology will also become the basis of the economic performance of nations, cultures, and civilizations. Civilizations tend to be competitive, and competitive civilizations tend to domination if not imperialism, and are prone to setting their own absolute standards for the rest of the world, thereby potentially contributing to perennial global tensions and violent eruptions. The depletion of natural resources will only make things worse unless humankind develops a mode of peaceful co-existence among civilizations. This modus vivendi will only become possible if world leaders in politics, religion and economics can develop a consensus based on trust (Fukuyama) and tolerance. Keywords: culture, civilization, plurality, value, relativity, absolutism, imperialism, dialogue, justice, co-existence Abstrak: Kebudayaan adalah totalitas ekspresi manusiawi menuju perwujudan dirinya baik secara individual maupun kolektif, dan selalu merupakan “tempat” (platform) untuk mencapai cita-cita hidupnya. Selama kebudayaan tidak dapat menghindarkan diri dari lingkup ruang dan waktu, selalu akan muncul pluralitas budaya serta relativitas nilai-nilai. Dinamika ini telah membawa umat manusia terkurung dalam apa yang disebut oleh Huntington sebagai “konflik peradaban-peradaban,” yakni, konflik nilai-nilai. Dunia abad ke-21 didominasi oleh “peradaban Barat,” peradapan Sinik, dan peradaban Islam. Kendati bahasa dan teknologi telah membuat manusia menjadi lebih dekat satu sama lain, bahasa dan teknologi juga akan menjadi landasan bagi citra ekonomi dari berbagai bangsa, kebudayaan-kebudayaan, dan peradaban-peradaban. Perdaban cenderung kompetitif, dan peradaban yang kompetitif cenderung menjadi sebuah dominasi, bahkan dapat menjadi imperial-isme. Akibatnya, mereka mudah tergelincir untuk menciptakan standar mereka yang abolut dan menerapkannya bagi seluruh dunia; karenanya, secara potensial menyumbang bagi munculnya ketegangan-ketegangan dan ledakan-ledakan kekerasan global yang perenial. Berkurangnya sumber-sumber alam hanya akan membuat situasi menjadi lebih buruk, kecuali bila manusia mengembangkan sebuah moda ko-eksistensi damai antarperadaban. Cara hidup (modus vivendi) seperti ini hanya dimungkinkan bila para pempimpin dunia di bidang politik, agama, dan ekonomi dapat mengembangkan sebuah konsensus berdasarkan kepercayaan dan toleransi. Kata-kata Kunci: kebudayaan, peradaban, pluralitas, nilai, relativitas, absolutisme, imperialisme, dialog, keadilan, ko-eksistensi.